Development of a broad-spectrum subunit vaccine against H9N2 avian influenza using HA stem domain scaffold and snoopligase system - Keji Quan; Nan Zhang; Mengqi Lin; Yuan Liu; Yue Li; Qun Hu; Maoshun Nie; Tao Qin; Sujuan Chen; Daxin Peng; Xiufan Liu (npj Vaccines)
Abstract H9N2 avian influenza virus (AIV) is a globally prevalent pathogen that causes economic losses in poultry and poses zoonotic threats. Due to antigenic drift and shift, traditional inactivated vaccines often show reduced efficacy. This study presents a novel subunit vaccine based on a conserved HA6 scaffold derived from the hemagglutinin stem domain and coupled with a fusion peptide epitope (fPE) via Snoopligase-mediated ligation. The HA6 protein was validated by its binding to the broad-spectrum antibody CR6261, and the fPE-HA6 fusion construct incorporated T- and B-cell epitopes. Immunization trials in a chicken demonstrated that fPE-HA6 induced stronger humoral and cellular immune responses than individual immunogens. Upon challenge with H9N2 strains YZ4 and SN, the fusion vaccine significantly reduced viral shedding, demonstrating broad-spectrum protection. These findings highlight the potential of HA6 as a modular scaffold for influenza vaccines and the utility of Snoopligase technology in developing broadly protective immunogens against antigenically variable viruses.